A New Approach For Expansion the Throughput Capacity of the Quick Response Code - Ali, Ammar Mohammed; Farhan, Alaa Kadhim (2019 First International Conference of Computer and Applied Sciences (CAS), 2019)
QR code has emerged as strong platforms, and powerful for a large-scale field of scientific and industrial processes.it can execute an essential part in addressing the subject of authentication. QR codes are applied in domains that affect the transfer of text information, and these include-mail messages, phone numbers, hyperlinks or another text file, This pursuit has thus been helpful in our knowledge towards obtaining an adequate and inexpensive method that does not require a high level of training. A key aspect of this work is thus to propose a new method to succeed in the deficiencies of the limited size of the traditional QR code. It relies on the features of the Shannon-Fano encoding algorithm to decrease the size of the input data and the principles of the XOR function. The main structure of this paper can be summarised in the following sections. First, it deals with the handling of an authentication system. The second section deals with the enhancement of the QR code to promote the data storage capacity. The last section of this paper deals with the display of the experiment's results and discusses. The suggested algorithm was explained in the schemes of several aspects, such as the secrecy aspect, the durability aspect, the complexity aspect, and the storage capacity. In this work, the proposed QR code does not reproduce the configuration or structure of the QR code. Indeed, the experimental results of this paper produced better findings of a great deal of the previous work.